Changes of phenolic acids and antioxidant activities during potherb mustard (Brassica juncea, Coss.) pickling - Fang, Zhongxiang; Hu, Y.; Liu, D.; Chen, J.; Ye, X. (Elsevier BV, 2008)
Phenolic acids in potherb mustard (Brassica juncea, Coss.) were determined and the effects of pickling methods on the contents of total free phenolic acids, total phenolic acids, total phenolics, and antioxidant activities were investigated. Gallic acid, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, caffeic acid, p-coumaric acid, ferulic acid, and sinapic acid were identified in the present study. The contents of total free phenolic acids, total phenolic acids and total phenolics in fresh potherb mustard were 84.8 ± 0.58 µg/g dry weight (DW), 539 ± 1.36 µg/g DW, and 7.95 ± 0.28 mg/g DW, respectively. The total free phenolic acids increased during the pickling processes, but the total phenolic acids, total phenolics, and antioxidant activities decreased. However, after 5 weeks of fermentation, all the pickling methods retained over 70% of total phenolic contents and above 65% of antioxidant capacities. The results indicated that pickling processes were relatively good methods for the preservation of phenolic acids and antioxidants for potherb mustard. © 2007 Elsevier Ltd. All rights reserved.